Cleaner Production Opportunities in Leather Tanning in Palestine - Al-Jabari, Maher; Sawalha, Hassan; Rene, Eldon R. (5th International Symposium on Environment and Morals, 2021)
Cleaner production (CP) options for leather manufacturing in Hebron are identified and eval uated for the purpose of examining their potential adoption. The approach was descriptive combined with field sampling and laboratory testing from seven factories. All processes in the investigated factories have been monitored, focusing on chromium contamination in wastewa ter (WW). In addition, pollution sources from every process have been identified, in a parallel paper, and used in this analysis. The determined process efficiency of tanning is found to be low to medium, compared to that reported in previous work. The evaluation of the identified CP options indicates that the most practical options is the improvement of operating conditions of the tanning process, such as pH, for increasing chromium uptake efficiency. This requires further experimental study to investigate the technical feasibility, industrial acceptance and the impacts of process modifications on the quality of the produced leather
Keywords: Leather, tanneries, wastewater, chromium, cleaner production